Orbital mechanics and formation flying : a digital control perspective - Capo-Lugo, Pedro A.; Bainum, Peter M. (Cambridge ; Philadelphia : Woodhead Pub., 2011)
Aimed at students, faculty and professionals in the aerospace field, this book provides practical information on the development, analysis, and control of a single and/or multiple spacecraft in space. This book is divided into two major sections: single and multiple satellite motion. The first section analyses the orbital mechanics, orbital perturbations, and attitude dynamics of a single satellite around the Earth. Using the knowledge of a single satellite motion, the translation of a group of satellites called formation flying or constellation is explained. Formation flying has been one of the main research topics over the last few years and this book explains different control approaches to control the satellite attitude motion and/or to maintain the constellation together. The control schemes are explained in the discrete domain such that it can be easily implemented on the computer on board the satellite. The key objective of this book is to show the reader the practical and the implementation process in the discrete domain. Explains the orbital motion and principal perturbations affecting the satelliteUses the Ares V rocket as an example to explain the attitude motion of a space vehiclePresents the practical approach for different control actuators that can be used in a satellite.
8.4 Linear quadratic regulator for attitude correction8.5 Linear quadratic regulator control weight design; 8.6 Suggested problems; 8.7 References; 9 Formation flying; 9.1 Introduction to formation flying; 9.2 Tschauner-Hempel formulation; 9.3 Clohessy-Wiltshire formulation; 9.4 Earth oblateness and solar effects in formation flying; 9.5 Lawden solution; 9.6 Discrete optimal control problem for formation flying; 9.7 Formation flying controller implementation; 9.8 Suggested problems; 9.9 References; 10 Deployment procedure for a constellation; 10.1 Introductory comments.
Includes bibliographical references and index.
Print version record.
Keywords: Orbital mechanics; Artificial satellites -- Control systems; Digital control systems; TECHNOLOGY & ENGINEERING -- Engineering (General); Artificial satellites -- Control systems; Digital control systems; Orbital mechanics